EDUKASI PENILAIAN STATUS GIZI UNTUK OPTIMALISASI PERTUMBUHAN ANAK BAGI SISWA SD NEGERI 22 ANDALAS KOTA PADANG - Yulizawati Yulizawati; Ulfa Farrah Lisa; Laila Rahmi; Uliy Iffah; Erda Mutiara Halida; Fitrayeni Fitrayeni; Aldina Ayunda Insani; Feni Andriani; Henni Fitria; Hindun Mila Hudzaifah; Dina Taufia; Laila Laila (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
A nutritional status assessment is a process undertaken to facilitating optimal development. Normal growth is defined as the optimal nutritional and health status, as indicated by conformity with the parameters set forth in growth charts. The objective of this activity is to gather data pertaining to the nutritional status of all students in grades IV, V, and VI of SDN 22 Andalas Padang, while concurrently imparting health education related to menarche as part of the students' overall growth and development. The assessment of nutritional status was conducted through the measurement of height and weight, with the calculation of the Body Mass Index and Age, of 110 students in grades IV, V, and VI of SDN 22 Andalas Padang. Additionally, health education about menarche was provided through presentations and the distribution of booklets. The results of the activity demonstrated a high level of acceptance and positive response from the teachers and leaders. The nutritional status of the students was found to be generally good, with only 4% of students having poor nutritional status, 80% having good nutritional status, 11% having overweight status, and 5% having obese nutritional status. Furthermore, the students displayed enthusiasm during the educational sessions. It can be concluded that the majority of SDN 22 Andalas Padang students have a normal nutritional status. Hopefully, this activity will form the basis for schools to carry out monitoring interventions for the nutritional status of school-age children and the continuation of regular activities by involving cross-sectoral partners.